A Research on a Comparative Study of Some Brand Switching Models in Marketing - Saran, Rashmita; Swamy, R. J. R. (Indian Journal of Marketing, 2018)
This study compared the static model (Hendry’s and SBS model) and dynamic model (DBS) of brand switching for predicting the future market shares ; also, it ascertained the consumer behavior of brand switching with regard to different demographic factors, identified the factors for brand switching among the different brands of packaged tea that are available in the market, and examined the relative importance of the factors on an overall satisfaction level of consumers and their repurchase intention. The methodologies used for the study are : chi square, exploratory factor analysis, and structural equation modeling. The research work found static nature of market for packaged tea, where DBS model was found to be the best for predicting the future market share. Functional benefit, brand reputation, and marketing efforts emerged as factors which positively influenced satisfaction ; whereas, heightened satisfaction level increased repurchase intention for the brands.